Incidence of the application of the google drive as an E-learning tool to develop the writing skill on students attending the eighth grades at Unidad Educativa Martim Cerré During the first quimestre of the 2013-2014 School year - León Pazmiño, Jorge Ignacio (2016)
WRITING is a necessary and basic skill that also helps an English learner become a good reader and speaker spontaneously. The refusal of learners to write in English is a problem found in ESL contexts, such as English classes and in the other content-based English subjects. Teachers of English and other English content-based subjects of this institution mentioned that learners develop a negative attitude to write paragraphs, letters, essays, and son on in English because they do not understand writing rules and sometimes they do not know rules to follow. Consequently, this research has been focused on using GOOGLE DRIVE in order to improve the writing production for students attending the eighth year of Basic Education at Unidad Educativa Martim Cererê. Once problems were detected, dependent and independent variables were determined in order to elaborate the objectives.